Colonization of Socorro Island (Mexico), by the tropical house gecko Hemidactylus frenatus (Squamata: Gekkonidae) - Galina-Tessaro, Patricia (Universidad de Costa Rica, 1999)
Hemidactylus frenatus Schlegel is a nocturnal lizard widely distributed in Southern Asia, the Pacific Islands, tropical Africa, Australia and Polynesia (Smith and Taylor 1950, Bustard 1970).